Standardidasi Simplisia dan Ekstrak Daun Walang (Etlingerawalang (Blume) R.M.Sm) Asli Banten - Novi, Cory (Journal of Chemistry Sciences and Education, 2024)
Walang is a plant an indigenous in Banten that belongs to the Zingberaceae family and is known to contain secondary metabolites that have potential as traditional medicine. Traditional raw materials need standardization. This study aims to standardize the simplisia and extract of walang leaves based on specific and non-specific parameters. The standardization method refers to the Indonesian Herbal Pharmacopoeia. The thick extract was obtained from the maceration of walang leaves using 70% ethanol with a yield of 3.634%. The results of organoleptic observations of simplisia are in the form of powder, green color, and distinctive odor, moisture content of 8.38%, ethanol soluble juice content of 3.90%, water soluble juice content of 3.90%, total ash content of simplisia 8.48% and acid insoluble ash content 12.02%. In contrast, the results of organoleptic observations of extracts are thick, green color and distinctive odor, moisture content of 2.17, ethanol soluble juice content of 2.58%, water-6soluble juice content of 2.36%, total ash content of extracts of 24.59% and acid insoluble ash content 27.52%. The results of specific and non-specific parameter tests of simplisia and walang leaf extract (Etlingera walang (Blume) R.M.Sm) some have met the requirements set by the Indonesian Herbal Pharmacopoeia and some have not met the requirements, namely total ash content and acid soluble content.